γδ T Cells’ Role in Donor-Specific Antibody Generation: Insights From Transplant Recipients and Experimental Models - Xavier Charmetant; Xavier Charmetant; Xavier Charmetant; Guillaume Rigault; Chien-Chia Chen; Hannah Kaminski; Hannah Kaminski; Jonathan Visentin; Jonathan Visentin; Benjamin Taton; Gabriel Marseres; Virginie Mathias; et al. (Transplant International)
The generation of donor-specific antibodies (DSA) requires that alloreactive B cells receive help from follicular helper T (TFH) cells. Recent works have suggested that γδ T cells could contribute to T cell-dependent humoral responses, leading us to investigate their role in DSA generation. Analysis of a cohort of 331 kidney transplant recipients found no relation between the number of circulating γδ T cells and the risk to develop DSA. Coculture models demonstrated that activated γδ T cells were unable to promote the differentiation of B cells into plasma cells, ruling out that they can be “surrogate” TFH. In line with this, γδ T cells preferentially localized outside the B cell follicles, in the T cell area of lymph nodes, suggesting that they could instead act as “antigen-presenting cell” (APC) to prime αβ TFH. This hypothesis was proven wrong since γδ T cells failed to acquire APC functions in vitro. These findings were validated in vivo by the demonstration that following transplantation with an allogeneic Balb/c (H2d) heart, wild-type and TCRδKO C57BL/6 (H2b) mice developed similar DSA responses, whereas TCRαKO recipients did not develop DSA. We concluded that the generation of DSA is unfazed by the absence of γδ T cells.